Bibliometric Computational Mapping Analysis of Publication On Bi2o3 Nanoparticles Using Vosviewer - Muhamad Daffa Putra (Institut Teknologi Dirgantara Adisutjipto, 2023)
This study examines the development of research on bismuth oxide (Bi2O3) nanoparticles through a bibliometric approach with computational mapping analysis using VOSviewer. Journal article data was obtained from the Google Scholar database using the Publish or Perish application. The keywords used to search related journals are Bi2O3, nanoparticles, chemistry, bismuth oxide. There were 998 journal articles related to keywords. The range of journal articles searched from the Google Scholar database is the last 10 years (2012 – 2022). The results show that research Bi2O3 nanoparticles can be separated into 3 terms: nanoparticle, Bi2O3, bismuth oxide. Nanoparticle term which is included in cluster 3 with 186 links total, 812 total link strength, and 163 occurrences. The second term is Bi2O3 which belongs to cluster 7 with a total of 213 links, a total link strength of 1550, and occurrences of 189 and a bismuth oxide term which belongs to cluster 4 with a total of 230 links, a total link strength of 2080, and 401 occurrences. The results of the analysis of research developments in the last 10 years show a slight fluctuation. In 2012 – 2013 there was an increase in the number of studies from 34 to 62 (28 studies). However, in 2013 – 2016 it decreased from 62 to 53 (9 studies). In 2016 – 2022 again experienced a significant increase from 53 to 152 (99 studies). With the results of this study, the development of research on Bi2O3 nanoparticles shows that this research has great opportunities that can be explored again.